SPECTRUM OF CT FINDINGS IN CLINICALLY SUSPECTED CASES OF MUCORMYCOSIS – A STUDY AT TERTIARY HEALTH-CARE CENTER (RAJINDRA HOSPITAL PATIALA) DURING SECOND WAVE OF COVID PANDEMIC - KUMARI, AMITA; BHATNAGAR, SIMMI; GUPTA, ISHITA; YADAV, VISHAV; MANPREET (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Rhinocereberal mucormycosis is an acute, fulminant, and often lethal opportunistic infection typically affecting diabetic or immunocompromised patients. Early diagnosis is vital in these infections because delay in initiation of the treatment can be life-threatening. Computed tomography (CT) with axial and coronal sections is a highly accurate and non-invasive modality to accurately image sinonasal mycosis. The aim of the study was to describe the imaging findings in suspected cases of mucormycosis on CT. Methods: This study was conducted in Radiodiagnosis Department of Rajindra Hospital, Patiala. The data of 22 patients who were referred for CT with a clinical suspicion of mucormycosis were collected and all these patients were followed up to know about the prognosis of the disease. Results: In our study, there were 54.60% females and 45.40% males. Maximum number of patients (45.45%) belonged to 40–49 year age group. Diabetes mellitus was found to be the most commonly (90.90%) found comorbidity followed by hypertension (36.36%). In our study, involvement of unilateral nasal cavity was observed in 36.36% cases. Among the paranasal sinuses, maxillary and ethmoid sinuses were the most commonly involved in 95.45% and 77.27% cases. Conclusion: Prompt diagnosis and treatment of rhino-orbital mucormycosis are the sine qua non as antifungal drugs and surgical debridement can successfully control the infection and thus reduce the high mortality and morbidity associated with mucormycosis.